Features of spring vegetation of hazel leaves in the foothills of the Republic of Adygea - E. K. Pchikhachev; T. A. Isushcheva (Новые технологии, 2021)
The article provides information about one of the areas of work associated with hazel carried out by the Adygh branch of the Federal State Budgetary Institution of Science «Federal Research Center «Subtropical Scientific Center of the Russian Academy of Sciences». The territorial location of this institution is the foothills of the Republic of Adygea, where the objects of the research, i.e. forms and varieties of hazel are located. The institution has been studying hazel since 1995. The article provides data on the collection site where the best forms and known varieties of hazel grow. At the collection site, phenological observations of hazel were carried out from 2017 to 2019. The information is given on the number of forms and varieties of hazel growing on the collection site, on the features of spring vegetation of leaves. The expression «spring vegetation of hazel leaves» implies several spring phenological phases of hazel, such as «beginning of leaf bud swelling»; «massive swelling of leaf buds»; «beginning of leaf bud opening» and «the maximum length of the leaf plate is 5 cm». The meteorological indicators of the studied period from 2017 to 2019 have been indicated. The article discusses the prospects of certain forms and varieties for various breeding purposes. Based on the data presented, it has been concluded that: 2017 was the most unfavorable of the three years of research in the meteorological plan; the earliest leaf vegetation during the three years of research was observed in the «Zakatala» variety; the leaf reaches 5 cm in the «Trapezund» variety and the «Futkurami» variety the very first, and the 20/15 form.